The room of white fire [compact disc, unabridged] : a novel - Parker, T. Jefferson (Books on Tape, 2017)
"From three-time Edgar Award winner and New York Times bestseller T. Jefferson Parker, a stirring new thriller about a private investigator tasked with hunting down a returned soldier broken and made dangerous by his experiences at war"--